2012
DOI: 10.1007/s10661-012-2661-6
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing and GIS-based integrated analysis of land cover change in Duzce plain and its surroundings (north western Turkey)

Abstract: The aim of this study is to research natural land cover change caused by the permanent effects of human activities in Duzce plain and its surroundings, and to determine the current status of the land cover. For this purpose, two Landsat TM images were used in the study for the years 1987 and 2010. These images are analysed by using data image processing techniques in ERDAS Imagine©10.0 and ArcGIS©10.0 software. Land cover change nomenclature is classified according to the Coordination of Information on the Env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Most studies have focused on LUCC analysis of environmental response and driving forces, but few have looked at land-use planning. Considering the spatial characteristics of land use, most investigators have used geospatial information system (GIS) RS as a research tool for preparing land-use maps, which is an intuitive approach to displaying planning programs [17]. Some have also set up scenarios and constructed models that integrate socioeconomic and ecological aspects to support land-use planning decisions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on LUCC analysis of environmental response and driving forces, but few have looked at land-use planning. Considering the spatial characteristics of land use, most investigators have used geospatial information system (GIS) RS as a research tool for preparing land-use maps, which is an intuitive approach to displaying planning programs [17]. Some have also set up scenarios and constructed models that integrate socioeconomic and ecological aspects to support land-use planning decisions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Similar case similar to Lu and Weng (2006) who also found that in low resolution image the water bodies or shadow and dark impervious surface [urban or built-up area] usually have undifferentiated spectral values and error in an estimation of impervious surface happened in the lessdeveloped area where there were mixture of impervious surfaces, vegetation and soil. Ikiel et al (2013) who used Landsat TM to study land cover change also support that the classification accuracy of the urban or built-up area was very low as a result of heterogeneous character of this area.…”
Section: Lulc Classificationmentioning
confidence: 81%
“…The total root mean square (RMS) error for this study was 4.5 m approximately, which is less than half the size of the pixel (15 m) [30,31]. The images were georeferenced using the Universal Transverse Mercator projection (UTM-49N, WGS-84) and resampled to 30 m spatial resolution [32]. The processing of remote-sensing satellite was carried out using the software package of Erdas Image V9.3 [33].…”
Section: Satellite Images Pre-processingmentioning
confidence: 99%